Prior metabolic surgery attenuates the weight-loss efficacy of liraglutide in patients with mild obesity - Ouyang, Yuqin; Xiang, Xinyue; Hu, Xinyun; Chu, Xuehui; Tang, Wenjuan; Feng, Wenhuan (Frontiers in Endocrinology, 2025)
BackgroundLiraglutide effectively manages mild obesity, but individual weight loss outcomes vary significantly. We aimed to identify clinical predictors influencing differential treatment responses in patients with mild obesity.MethodsA retrospective analysis was conducted on 64 adults (BMI 28–32.5 kg/m²) undergoing a 12-week liraglutide intervention. Participants were categorized based on therapeutic success: those achieving composite endpoints (≥5% total weight loss [TWL] and BMI normalization to <28 kg/m²) versus suboptimal responders. Comprehensive biometric and biochemical assessments were performed, and multivariate predictive modeling was applied.ResultsResponders (n=37, 75.7% female) showed significantly better metabolic outcomes than non-responders (n=27, 77.8% female), with notable differences in %TWL (11.0 ± 3.6% vs 4.2 ± 2.6%), total weight loss (9.04 ± 3.32 kg vs 3.55 ± 2.20 kg), and BMI reduction (3.3 ± 1.1 vs 1.4 ± 0.9 kg/m²) (all p’s <.01). Responders also demonstrated improved glucolipid metabolism, and reduced metabolic-associated fatty liver disease (p <.05). Regression analysis identified a history metabolic surgery (MS) and a baseline BMI ≥30.5 kg/m² as significant negative predictors of success. Adjusted odds ratios indicated strong inverse associations, with MS history showing an OR of 6.78 (95% CI: 1.95–23.61; p <.01) and elevated BMI (≥30.5 kg/m²) yielding an OR of 4.79 (95% CI: 1.46–15.71; p <.01).ConclusionA history of MS significantly affects liraglutide’s responsiveness in patients with mild obesity, emphasizing the need for personalized therapeutic strategies in post-surgical patients. These findings highlight the importance of a comprehensive medical history in guiding obesity pharmacotherapy.